What is the length of the hypotenuse of a right triangle whose legs have lengths of 5 and 12?

The length of the hypotenuse of a right triangle whose legs have lengths of 5 and 12 is sqrt (5^2 + 12^2) = 13

s

Question

Asked 4/28/2015 11:47:56 AM

Updated 4/29/2015 9:05:10 PM

1 Answer/Comment

Rating

8

The length of the hypotenuse of a right triangle whose legs have lengths of 5 and 12 is sqrt (5^2 + 12^2) = 13

Added 4/29/2015 9:05:10 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [5/5/2015 10:04:10 AM]

2x 2 - 2x - 1 = 0
**Weegy:** (2x - 1)(x + 5) = 0; 2x - 1 = 0; 2x = 0 + 1; 2x = 1; x = 1/2; x + 5 = 0; x = 0 - 5; x = -5; the solution set is (1/2, -5) **User:** x 2 + 5x + 4 = 0
**Weegy:** 2x - 1 **User:** 5x2 + 7x = 6 (More)

Question

Updated 5/4/2015 10:08:20 PM

3 Answers/Comments

2x^2 - 2x - 1 = 0

a = 2, b = -2, c = -1

b^2 - 4ac = (-2)^2 - 4(2)(-1) = 4 + 8 = 12

x = [-b ± sqrt (b^2 - 4ac)]/2a

= (2 ± sqrt 12)/4

= (2 ± 2 sqrt 3)/4

= (1 ± sqrt 3)/2

a = 2, b = -2, c = -1

b^2 - 4ac = (-2)^2 - 4(2)(-1) = 4 + 8 = 12

x = [-b ± sqrt (b^2 - 4ac)]/2a

= (2 ± sqrt 12)/4

= (2 ± 2 sqrt 3)/4

= (1 ± sqrt 3)/2

Added 5/4/2015 10:06:24 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [5/5/2015 9:59:11 AM]

x^2 + 5x + 4 = 0

(x + 1)(x + 4) = 0

x = -1 or x = -4

(x + 1)(x + 4) = 0

x = -1 or x = -4

Added 5/4/2015 10:07:03 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [5/5/2015 9:59:38 AM]

A parabola has a vertex at (-1, 0) and opens down. What is the equation of the parabola?
y = -x2 - 1
y = -(x - 1)2
y = -(x + 1)2 User: Which of the following equations is of a parabola with a vertex at (3, 0)?
y = (x - 3)2
y = (x + 3)2
y = x2 - 3
y = x2 + 3 User: Which of the following equations is of a parabola with a vertex at (3, 0)?
y = (x - 3)2
y = (x + 3)2
y = x2 - 3
y = x2 + 3 User: A parabola whose equation is y = (x - 5)2 - 2 has a vertex at _____.
(-5, -2)
(-5, 2)
(5, -2)
(5, ...

Question

Updated 5/4/2015 8:30:18 AM

3 Answers/Comments

y = (x - 3)^2 is of a parabola with a vertex at (3, 0).

Added 5/4/2015 8:28:28 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [5/5/2015 10:04:59 AM]

A parabola whose equation is y = (x - 5)^2 - 2 has a vertex at (5, -2)

Added 5/4/2015 8:29:12 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [5/5/2015 10:07:52 AM]

Find the vertex of the parabola whose equation is y = -2x2 + 8x - 5. User: Find the vertex of the parabola whose equation is y = x2 + 6x + 2. User: y = -x2 - 4x - 3 User: Which of the following is a quadratic inequality?
y **Weegy:** y **User:** The dashed parabola is to the quadratic inequality as the is to the number line graph.
**Weegy:** That would be open circle **User:** A parabola opens down if the value of is negative in the general form of the equation. (More)

Question

Not Answered

Updated 4/29/2015 9:56:42 PM

3 Answers/Comments

A parabola opens down if the value of "a" is negative in the general form of the equation.

Added 4/29/2015 9:53:17 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [4/30/2015 2:55:59 AM]

The vertex of the parabola whose equation is y = x^2 + 6x + 2 is (-3, -7).

Added 4/29/2015 9:55:17 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [4/30/2015 2:56:23 AM]

Give the values of a, b, and c from the general form of the equation (2x + 1)(x - 2) = 0.
User: Which of the following equations is quadratic?
x(x2 + 1) = 0
5(4x + 2) = 3
(x + 3)(x + 4) = 5 User: Which of the following is the general form of the equation 5x2 - 20x = 15? **Weegy:** The general form of the equation 5x^2 - 20x = 15 is 5x^2 - 20x - 15 = 0. **User:** The line of symmetry of the parabola whose equation is y = ax2 - 4x + 3 is x = -2. What is the value of "a"? **User:** Describe the translation of the graph of y = x2 that results in the graph of y = (x - 3)2. (More)

Question

Not Answered

Updated 4/29/2015 8:49:57 PM

3 Answers/Comments

(x + 3)(x + 4) = 5 is quadratic.

(x + 3)(x + 4) = 5

x^2 + 3x + 4x + 12 = 5

x^2 + 7x + 7 = 0

(x + 3)(x + 4) = 5

x^2 + 3x + 4x + 12 = 5

x^2 + 7x + 7 = 0

Added 4/29/2015 8:47:58 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [4/30/2015 1:50:55 PM]

The line of symmetry of the parabola whose equation is y = ax^2 - 4x + 3 is x = -2. -1 is the value of "a".

4/2a = -2

4 = -4a

a = -1

4/2a = -2

4 = -4a

a = -1

Added 4/29/2015 8:49:02 PM

3 units right is the translation of the graph of y = x^2 that results in the graph of y = (x - 3)^2.

Added 4/29/2015 8:49:57 PM

32,746,945

questions answered

There are no comments.